Rate of CO2 transfer to loaded MEA solutions using a membrane contactor device. (September 2016) - Comite, Antonio; Costa, Camilla; Demartini, Marco; Di Felice, Renzo; Rotondi, Marco
Highlights: CO2 transfer rates from a gas stream to a MEA solution were investigated. The use of a membrane contactors allowed for a stable well-defined gas-liquid interface. CO2 partial pressure, MEA concentration, MEA loading, temperature were the variables investigated. The results could be well reproduced with a simple model based on published relationships with no empirical fitting constants. Abstract: Rates of carbon dioxide (CO2 ) transfer from a gas phase to loaded monoethanolamine (MEA) solutions were experimentally investigated for a wide range of operating conditions (CO2 partial pressure, MEA concentration, CO2 loading, temperature) using a membrane contactor in order to assess the best operating settings. Simultaneously a simple diffusion/reaction mathematical model was set up which, by making use of published physical and chemical parameters, described in a more than satisfactory manner the observed process rates.